Microcatchments increase yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Farmers in Somalia's northwest region have recently completed trials which show that a new water retention system increases their yields for less work. Farmers had been using standard bunds to conserve soil and use available rainfall more...